2020
DOI: 10.2147/idr.s253380
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of CRISPR/Cas System with the Drug Resistance in <em>Klebsiella pneumoniae</em></p>

Abstract: Background: Klebsiella pneumoniae is a common opportunistic pathogen and its production of extended-spectrum β-lactamases (ESBL) and carbapenemases leads to drug resistance. Clustered regularly interspaced short palindromic repeats (CRISPRs) and their associated genes (Cas) are widespread in the genome of many bacteria and are a defense mechanism against foreign invaders such as plasmids and viruses. Purpose: To investigate the prevalence of the CRISPR/Cas system in wild type strains of K. pneumoniae in the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 24 publications
4
35
1
1
Order By: Relevance
“…The study by Aydin et al suggested that the CRISPR-Cas system may interfere with the acquisition of resistant plasmids, thereby maintaining the sensitivity of these strains ( 9 ). Klebsiella pneumoniae strains detected that the spacers in the CRISPR array matched the genome of the plasmid or phage, some containing resistance genes ( 29 ). In Francis bacteria , CRISPR-Cas can enhance the integrity of its envelope, leading to resistance to several membrane stressors, including antibiotics, and increasing antibiotic resistance ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Aydin et al suggested that the CRISPR-Cas system may interfere with the acquisition of resistant plasmids, thereby maintaining the sensitivity of these strains ( 9 ). Klebsiella pneumoniae strains detected that the spacers in the CRISPR array matched the genome of the plasmid or phage, some containing resistance genes ( 29 ). In Francis bacteria , CRISPR-Cas can enhance the integrity of its envelope, leading to resistance to several membrane stressors, including antibiotics, and increasing antibiotic resistance ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genotype of drug resistance was screened by PCR for carbapenemase genes ( blaKPC, blaNDM, blaIMP, blaVIM, blaSME, blaGES ), ESBL genes ( blaCTX-M, blaTEM, blaSHV ) and AmpC genes ( blaFOX, blaDHA, blaMOX, blaCIT, blaACC, blaEBC ). 26 Then, DNA sequencing was conducted by Sangon (Shanghai, China). The PCR results were validated by nucleotide BLAST searches using GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of the CRISPR-Cas system has been found to have a highly substantial negative association with the antibiotic resistance in some bacteria. 13 , 14 However, very few studies have addressed this issue so far, and even in some of them, a positive association has been reported. 9 Hence, this study aimed to evaluate the presence of CRISPR-Cas system genes and their possible association with antibiotic resistance patterns of E. faecalis and E. faecium isolated from HWW samples of several hospitals.…”
Section: Introductionmentioning
confidence: 99%